COMMUNITY BASED E-MARKETING: PEMASARAN ONLINE BERBASIS KOMUNITAS BAGI IKM MINAPOLITAN PATUGURAN REJOSO PASURUAN - Khafizh Rosyidi (LPPM Universitas Yudharta Pasuruan, 2018)
Sea and fisheries are a great potential in Indonesia. Many national development policies and programs are directed towards this sector. Along with the development of information and communication technology that is so fast now, the development policies and programs of the sea sector and fisheries require adjustments, especially in terms of adopting digital-based technology in order to meet the economic needs of the community. The rapid development of technology, the digital world and the internet certainly has an impact on the world of marketing. Digital marketing or marketing done online is also called e-marketing. Market digitalization with the current e-marketing model has become a crucial point in daily activities, including business activities. The indication is the growth of smartphone or android ownership that provides easy internet access, the large number of social media users such as Facebook, WhatsApp, Instagram, and so on. The Micro, Small and Medium Enterprises (MSMEs) unit that contributes 61.41% of the national Gross Domestic Product (GDP) is a major power of the Indonesian economy. However, of that amount, 90% of MSME units are still running in the offline domain, even though the data in January 2016 stated that the infrastructure potential of Information and Communication Technology (ICT) covers around 90% of the population with more than 126% mobile penetration rates with internet users reaching 51.8% of the total population of Indonesia. In the preliminary study it was found that there were 45 MSMEs processing seafood and fisheries in the Minapolitan area of Pasuruan Regency assisted by the Indonesian Fishermen Association (HNSI), 11 of which were in Rejoso District. This is because HNSI Pasuruan Regency is headquartered in Patuguran Village, Rejoso District. However, the productivity of a number of MSMEs is still seasonal, due to the very limited market access. Why not, most of these MSMEs are still running offline or conventional. The limitations of skills and information technology tools in the form of smartphones or androids become an obstacle in their development efforts. HNSI Pasuruan Regency was chosen as the first partner in this community partnership program, because HNSI is an organization that is quite intense in conducting guidance for MSMEs, especially in the Minapolitan area of Pasuruan Regency. In addition, the Head of Patuguran Village was chosen as partner II in this community partnership program, because at the end of 2017 he had been awarded the "Maslahat Award" in MSME in Pasuruan Regency.